Memanfaatkan Instagram untuk Kampanye Politik: Strategi dan Dampaknya di Sumatera Barat - Jibril Dihya Azzikra, Muhammad; Dinanti, Mutiara; Rusta, Andri; Fajri, Muhammad; Irawati (Jurnal Administrasi Publik dan Pemerintahan, 2024)
Globalization and technological advancements have transformed communication methods, including strategies for political campaigns. This study examines the role of Instagram as a social media platform in shaping political party campaign strategies in West Sumatra. Employing a literature review methodology, the findings reveal that Instagram’s visually engaging and interactive features have been instrumental for political parties in building personal branding, expanding audience reach, and enhancing public engagement. Tactics such as visual content optimization, hashtag campaigns, and influencer collaborations have proven effective. Data on internet and social media penetration in West Sumatra indicates that Instagram is a powerful tool for connecting with the public. The study highlights how political parties like Gerindra have successfully utilized Instagram to achieve significant audience engagement compared to their competitors. Furthermore, it underscores how the integration of technology into political campaigns not only broadens outreach but also improves the overall effectiveness of campaign strategies.